SISTEM KEAMANAN LOKER DENGAN FINGERPRINT DAN RFID BERBASIS WEBSITE - Tri Saputra, Egi; Pratama, Vargas; Saputra, Zanu; Irwan, Irwan (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
A locker is a place used to store items such as clothes, books, documents, and others. Technological developments in security systems are also very necessary, especially in security systems for storing goods and documents in lockers. The security system on traditional lockers that are widely circulated today is still conventional, in the sense that the security of the locker door still uses a manual locking mechanism and there are many ways of hacking to open the locker easily, which is less safe and efficient. The results of this study indicate that the locker system with dual security is very effective for security in storing goods, with the existence of this system in addition to the owner who uses the locker can not open the locker by guessing like in lockers in general that are still conventional, with this system requires fingerprint identification (scan fingerprint) and wireless card (RFID) to open the safe.